Clear Cell Myoepithelial Carcinoma Arising from the Hard Palate with Metastasis to the Lungs - Jiayun Fang; Amanda Kornfield; Alex Clavijo; Shikhar Vyas; Alison Ulbrandt; Carsten Schroeder; J. Kenneth Byrd; Daniel Kleven (Case Reports in Pathology)
Myoepithelial carcinoma is an uncommon tumor of the salivary glands, most commonly the parotid gland. Clear cell myoepithelial carcinoma is a rare variant with an aggressive behavior. Here, we describe a case of clear cell myoepithelial carcinoma arising from the hard palate in an elderly male who underwent resection of the tumor and postop radiation. Posttreatment imaging demonstrated bilateral pulmonary nodules and a C2 body lesion concerning for metastasis. Biopsy of the lung lesions revealed a monomorphous population of optically clear cells with hyperchromatic and pleomorphic nuclei which were morphologically similar to the prior resection specimen. There are few reported cases of clear cell myoepithelial carcinoma arising from the hard palate, and there are even fewer reports on metastases to the lungs. Due to the low number of reported cases, prognosis and treatment of this neoplasm is not well defined.